Isolated Fallopian Tube Torsion. (30th July 2013) - Kardakis, S.; Barranca, A.; Vitelli, A.; Amore, I.; Trento, F.; Caccia, G.
Abstract : Isolated torsion of the Fallopian tube is a rare gynecological cause of acute lower abdominal pain, and diagnosis is difficult. There are no pathognomonic symptoms; clinical, imaging, or laboratory findings. A preoperative ultrasound showing tubular adnexal masses of heterogeneous echogenicity with cystic component is often present. Diagnosis can rarely be made before operation, and laparoscopy is necessary to establish the diagnosis. Unfortunately, surgery often is performed too late for tube conservation. Isolated Fallopian tube torsion should be suspected in case of acute pelvic pain, and prompt intervention is necessary.